Independent Control of Temperature and Humidity in Air Conditioners by Using Fuzzy Sliding Mode Approach. (4th August 2020) - Yang, Lijian; Li, Ziyang; Wu, Zhengtian; Xie, Mingyang; Jiang, Baoping; Fu, Baochuan
Abstract : This paper proposes a sliding mode control (SMC) strategy to solve the problem of independent control of temperature and humidity in air conditioners; the complexity increases due to the need to make full use of the wind side for cooling. First, dynamics of indoor temperature and humidity are determined based on mathematical models. Second, in order to reduce the chattering effect of SMC and coordinate indoor conditions to satisfy people's needs, the independent control of temperature and humidity is realized via a novel fuzzy sliding mode control strategy based on reaching laws. Finally, simulation results are provided to verify the effectiveness of the proposed method.